Could sex differences in white matter be explained by g ratio? - Paus, Tomas; Toro, Roberto (Frontiers in Neuroanatomy, 2009)
Recent studies with magnetic resonance imaging suggest that age-related changes in white matter during male adolescence may indicate an increase in g ratio wherein the radial growth of an axon outpaces a corresponding increase in myelin thickness. We review the original Rushton (1951) model where a g ratio of 0.6 represents an optimal relationship between the axon and fibre diameters vis-à-vis conduction velocity, and point out evidence indicating slightly higher g ratio in large-diameter fibres. We estimate that fibres with a diameter larger than 9.6 µm will have a relatively thinner myelin sheath, and brains with increasingly larger proportions of such large-diameter fibres will have progressively lower concentration of myelin. We conclude by pointing out possible implications of “suboptimal” g ratio for the emergence of “disconnection” disorders, such as schizophrenia, in late adolescence.